HEMI-MAXILLECTOMY RESTORED WITH HOLLOW BULB CAST PARTIAL OBTURATOR - Patil, Dr. Rahul (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2016)
Throughout recorded history, it is evident that man has found a need toattempt to restore or replace the eyes and facial parts of those who were eitherunfortunate enough to have congenital deformities, or to have suffered fromtrauma or disease.The definition is quite broad. It could include such important dentalspecialties as fixed and removable prosthodontics, since these specialties alsodeal with replacing missing tissues. Yet, the term is used to imply only thoseintraoral, para oral or extraoral areas that are not within the scope of these otherdental specialties.Many phases of maxillofacial prosthetics are merely logical extensions ofprosthodontics to those areas that are part of them. The basic material andtechniques used in both fields are also similar. The success, like in prosthodonticsdepends on full cognizance of the principles that underlie facial harmony, colormatching, anchorage and retention, weight bearing and leverage, durability andstrength of materials used, tissue compressibility and tissue tolerance.